Human-Centered Leadership in the Digital Era: Examining the Role of Psychological Capital in Managerial Coaching Outcomes - Dewiana Novitasari; Felina C. Young (International Journal of Management and Economic Research (IJOMER), 2025)
The accelerating transformation of Industry 4.0 has increased the strategic importance of developmental leadership practices capable of strengthening employee adaptability, resilience, and performance. This study investigates the role of managerial coaching as a human-centered leadership approach in enhancing employee performance, with psychological capital serving as the key mediating mechanism. Drawing on Organizational Support Theory (OST), Conservation of Resources Theory (COR), and Positive Organizational Behavior (POB), the study examines how coaching behaviors stimulate employees’ internal psychological resources—hope, efficacy, optimism, and resilience—in digitally intensive workplaces. Using a quantitative survey of 224 employees in a manufacturing firm in Indonesia, data were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that managerial coaching exerts a positive and significant direct effect on employee performance and an indirect effect through psychological capital. Psychological capital emerged as a strong mediator, indicating that employees who receive developmental coaching are more capable of activating positive psychological resources that translate into superior performance. This study extends existing coaching literature by integrating contemporary psychological frameworks and highlights managerial coaching as a critical strategy for developing high-performing and future-ready human capital in the digital era. Practical implications encourage organizations to institutionalize coaching cultures and invest in psychological resource development to sustain competitiveness in Industry 4.0.